Answer:
![\frac{23}{28}](https://tex.z-dn.net/?f=%20%5Cfrac%7B23%7D%7B28%7D%20)
Step-by-step explanation:
![\frac{2}{3} \times \frac{3}{4} + \frac{3}{7} \times \frac{3}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B3%7D%20%20%5Ctimes%20%20%5Cfrac%7B3%7D%7B4%7D%20%20%2B%20%20%5Cfrac%7B3%7D%7B7%7D%20%20%5Ctimes%20%20%5Cfrac%7B3%7D%7B4%7D%20)
![= > \frac{3}{4} ( \frac{2}{3} + \frac{3}{7} )](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20%20%5Cfrac%7B3%7D%7B4%7D%20%28%20%5Cfrac%7B2%7D%7B3%7D%20%20%2B%20%20%5Cfrac%7B3%7D%7B7%7D%20%29)
![= > \frac{3}{4} \times \frac{23}{21}](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20%20%5Cfrac%7B3%7D%7B4%7D%20%20%5Ctimes%20%20%5Cfrac%7B23%7D%7B21%7D%20)
Reducing 3 from numerator and denominator,
![= > \frac{23}{4 \times 7} = \frac{23}{28}](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20%20%5Cfrac%7B23%7D%7B4%20%5Ctimes%207%7D%20%20%3D%20%20%5Cfrac%7B23%7D%7B28%7D%20)
Answer:
<em>Y = -4/3</em>
Step-by-step explanation:
Subtract 1 from -1/3.
Y = -1/3 - 1
Y = -1/3 - 3/3
Y = -4/3
In any equation there is a variable (usually x). In a quadratic equation there is a lot involved.
-B (+or-) sqrt of b^2 - 4 x A x C
________________________ divide it by
2 x A
There is usually an original equation that looks like: Ax^2 + Bx + C = 0 Use the variables from the equation to the left to fill the upper equation. (You can also look up a better formula if confused).